The girls : a novel - Cline, Emma (Random House, 2016)
Mesmerized by a band of girls in the park whom she perceives as enjoying a life of free and careless abandon, 1960s teen Evie Boyd becomes obsessed with gaining acceptance into their circle. Evie, grateful for their charismatic leader's attention, the sense of family the group offers, and the assurance of the girls, is swept into their chaotic cult existence. As things turn darker, her choices become riskier. A wonderfully written debut novel about the harm we can do, to ourselves and others, in our hunger for belonging and acceptance. --